Interactive game “Kahoot!” as the media of students’ vocabulary assessment - Hadijah Hadijah; Bambang Widi Pratolo; Rondiyah Rondiyah (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2020)
This research aims to investigate students’ perspectives on using the interactive game “Kahoot!” as the media of vocabulary test at one of the public senior high schools in Yogyakarta Indonesia. It was qualitative research with five voluntarily participating students as the participants. An in-depth semi-structured interview was applied as the data collection technique. The theme-based analysis was used in this study. The finding shows that first, Kahoot! is more practical for a vocabulary test. Second, the game can attract the students’ attention to the test. Third, it helps the students to be more active in the classroom and the last, the game makes the students more enthusiastic in doing the test. However, this research also found some negative sides of using Kahoot!; first, the students become less confident with their score, especially when they get lower scores than other students because the scores were displayed on the leader board in Kahoot! application; second, some students had a lack of knowledge in using the application; and the last, the time was limited. This study implies that the use of Kahoot! in the EFL classroom can be an alternative for teachers to teach vocabulary and provide fun learning activities for the students.